2016
DOI: 10.1152/japplphysiol.00511.2015
|View full text |Cite
|
Sign up to set email alerts
|

Triceps surae muscle-tendon properties in older endurance- and sprint-trained athletes

Abstract: Previous studies have shown that aging is associated with alterations in muscle architecture and tendon properties (Morse CI, Thom JM, Birch KM, Narici MV. Acta Physiol Scand 183: 291-298, 2005; Narici MV, Maganaris CN, Reeves ND, Capodaglio P. J Appl Physiol 95: 2229-2234, 2003; Stenroth L, Peltonen J, Cronin NJ, Sipila S, Finni T. J Appl Physiol 113: 1537-1544, 2012). However, the possible influence of different types of regular exercise loading on muscle architecture and tendon properties in older adults is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 50 publications
4
50
1
1
Order By: Relevance
“…Fascicle lengths and pennation angles fall within the range previously reported on cadaver muscles (Agur et al, 2003, Ward et al, 2009, Spoor et al, 1991 and in vivo using ultrasound (Stenroth et al, 2016, Kawakami et al, 1998, Maganaris, 2001, Maganaris et al, 1998. Although fascicle lengths between compartments were similar, there was considerable variation in average fascicle lengths between subjects, ranging from 29 to 51 mm at the short muscle length and 37 to 61 mm at the long length.…”
Section: Discussionsupporting
confidence: 81%
“…Fascicle lengths and pennation angles fall within the range previously reported on cadaver muscles (Agur et al, 2003, Ward et al, 2009, Spoor et al, 1991 and in vivo using ultrasound (Stenroth et al, 2016, Kawakami et al, 1998, Maganaris, 2001, Maganaris et al, 1998. Although fascicle lengths between compartments were similar, there was considerable variation in average fascicle lengths between subjects, ranging from 29 to 51 mm at the short muscle length and 37 to 61 mm at the long length.…”
Section: Discussionsupporting
confidence: 81%
“…In their study, it was found that the sprinters also had significantly higher MVC torque values (154.6 Nm) than the endurance athletes (126.3 Nm). Stenroth et al (2015) found a tendency for higher MVC torque in older sprinters (153 Nm) compared to older endurance athletes (age of both groups around 74 years; 116 Nm). In the present study, both the goalkeepers (156.6 Nm)and the midfielders (160.6 Nm) had similar torque values to the sprinters in the study of Arampatzis et al (2007).…”
Section: Discussionmentioning
confidence: 80%
“…Regarding further parameters of the MTU, Arampatzis et al (2007), in a study of active track and field athletes, but not Stenroth et al (2015), in a study of older athletes, found stiffer tendons in the sprinter group than in the endurance and non-active groups. Due to the explosive characteristic of goalkeeper movements (similar to the sprinters in the study of Arampatzis et al (2007)), we expected that goalkeepers would have stiffer tendons and/or muscles than midfielders and the controls.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations